Global Positioning System (GPS): The Utilization of GPS in Commercial Vehicle Licensing Board (LPKP) (Global Business Management Review (GBMR), 2012)
This research will be a feasibility study of the utilization of Global Positioning System (GPS) in Lembaga Pelesenan Kenderaan Perdagangan (LPKP). GPS is a widely use technology in various sectors such as military, civilian and others, however in this research the focus would be on the transportation vehicles that are being registered with LPKP. The GPS will not only be used for tracking and controlling but it will be used to locate the location of the vehicle but capable of recording the handling errors of the drivers. The objective of this research is to find out any issues that will arise from the future utilization of the technology, focusing on the transportation’s operators. Thus, it could be used as a feedback for the LPKP to take into consideration of the issues.